Los errores de los padres en la educación de sus hijos y el desarrollo del área social de las niñas y niños del primer año de educación básica de la escuela fiscal mixta Lauro Damerval Ayora n° 1 de la ciudad de Loja, período 2011 – 2012 - Chávez Duchi, Cristina Alexandra (2013)
This thesis refers to ERRORS OF PARENTS IN EDUCATION OF THEIR CHILDREN AND SOCIAL DEVELOPMENT AREA OF CHILDREN FIRST YEAR BASIC EDUCATION SCHOOL MIXED FISCAL AYORA DAMERVAL LAURO N° 1 LOJA CITY, PERIOD 2011 - 2012. The overall objective was to analyze parents influence their children's mistakes in the social area of the children from the First Year of Basic Education. The methods used for the development of this research work was the scientific method, the analytical method and the inductive method, the techniques used were the surveys of parents and teachers the first year of basic education for the errors of the parents. The field research was carried out with a total of 48 boys and girls, as parents and teachers. From the information obtained through the use of surveys, it was concluded that 26% of parents have poor communication, 23% emotional manipulation, in addition to the 15% found that parents fill the gaps with elements materials, 12% overprotection, and likewise found factors such as the misuse of authority with 8% and 7% finally found the management of new technologies.